PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, MORALITAS APARAT DAN ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Amalia, Reda Dista; -, Kamaliah; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of Influence Effectiveness of Internal Control, Compliance Compensation, Morality Apparatus and Information Asymmetry on Accounting Fraud Trends. This research was conducted by using descriptive method survey. Collecting data in this study are primary data obtained from questionnaires distributed directly to the respondents. Sample selection technique is purposive sampling. The sample used in this study were 61 respondents who served as the fourth echelon in the regional work units (SKPD) in Siak Sri Indrapura. Management and analysis of data using multiple linear regression analysis with the help of software SPSS version 20 (Statistical Product and Service Solution). Hypothesis testing results indicate that effectiveness of internal control, suitability of the compensation and apparatus morality negative effect on the tendency of accounting fraud and information asymmetry positive effect on the tendency of accounting fraud. The coefficient of determination in this study was 62.2%, while 37.8% is influenced by other variables.Keywords: Internal Control, Compensation, Morality, Information and Accounting Fraud